DESIGNING FOR THE MAKING OF CONCERT EVENT WITH JAVA MUSIKINDO ADOBE PHOTOSHOP CREATIVE SUITE 2 - Febrianto Handri Sasongko; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2009)
The development of computer technology has been growing rapidly in the first place has a function as a tool in resolving issues and problems in all fields and then enter the function as a multi -design. The design world is a lonely world behind the scenes during these publications seen by everyone. Design also involves many details that need precision, persistence, and patience in managing every element - element to be a unity of design in view and at the same time conveying a message effectively.